Amyloid-β-induced alteration of fast and localized calcium elevations in cultured astrocytes - Kaito Nakata; Joe Sakamoto; Kohei Otomo; Masanao Sato; Hirokazu Ishii; Motosuke Tsutsumi; Ryosuke Enoki; Tomomi Nemoto (Scientific Reports)
Abstract Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that causes cognitive decline. Uncovering the mechanisms of neurodegeneration in the early stages is essential to establish a treatment for AD. Recent research has proposed the hypothesis that amyloid-β (Aβ) oligomers elicit an excessive glutamate release from astrocytes toward synapses through intracellular free Ca2+ ([Ca2+] i ) elevations in astrocytes, finally resulting in neuronal dendritic spine loss. Under physiological conditions, astrocytic [Ca2+] i elevations range spatially from microdomains to network-wide propagation and temporally from milliseconds to tens of seconds. Astrocytic localized and fast [Ca2+] i elevations might correlate with glutamate release; however, the Aβ-induced alteration of localized, fast astrocytic [Ca2+] i elevations remains unexplored. In this study, we quantitatively investigated the Aβ dimers-induced changes in the spatial and temporal patterns of [Ca2+] i in a primary culture of astrocytes by two-photon excitation spinning-disk confocal microscopy. The frequency of fast [Ca2+] i elevations occurring locally in astrocytes (≤ 0.5 s, ≤ 35 µm2) and [Ca2+] i event occupancy relative to cell area significantly increased after exposure to Aβ dimers. The effect of Aβ dimers appeared above 500 nM, and these Aβ dimers-induced [Ca2+] i elevations were primarily mediated by a metabotropic purinergic receptor (P2Y1 receptor) and Ca2+ release from the endoplasmic reticulum. Our findings suggest that the Aβ dimers-induced alterations and hyperactivation of astrocytic [Ca2+] i is a candidate cellular mechanism in the early stages of AD.